Atorvastatin and ezetimibe protect against hypercholesterolemia-induced lung oxidative stress, inflammation, and fibrosis in rats - Seenak, Porrnthanate; Kumphune, Sarawut; Prasitsak, Thanit; Nernpermpisooth, Nitirut; Malakul, Wachirawadee (Frontiers in Medicine, 2022)
Background Hypercholesterolemia is a major risk factor for interstitial lung disease (ILD). Atorvastatin and ezetimibe are antilipemic drugs that have pleiotropic effects. However, their effects on pulmonary fibrosis prevention and the mechanisms underlying hypercholesterolemia have not been fully investigated. This study aimed to evaluate the individual effects of atorvastatin and ezetimibe on lung inflammation and fibrosis in high-cholesterol diet (HCD)-fed rats. Materials and methods Male Sprague-Dawley rats were divided into four groups — standard diet (S), standard diet + 1% cholesterol (SC), standard diet + 1% cholesterol with 30 mg/kg/day atorvastatin (SCA), and standard diet + 1% cholesterol with 10 mg/kg/day ezetimibe (SCE). At the end of an 8-week dietary schedule, serum lipid parameters and the levels of lung oxidative stress, inflammatory cytokines, and fibrotic mediators were determined. Results Atorvastatin and ezetimibe treatment remarkably reduced serum lipid profiles with reversed pulmonary histological alterations, in addition to reducing the levels of lung oxidative stress, inflammation, and fibrosis in hypercholesterolemic rats. Conclusion Atorvastatin and ezetimibe treatment showed a protective effect against hypercholesterolemia-induced pulmonary fibrosis in rats. This information appears potentially useful in the prevention of PF in a hypercholesterolemia model; however, further rigorous investigations are needed to prove their clinical utility on antifibrosis.